Understanding how grade 11 Physical Science teachers mediate learning of the topic distillation in the Kavango Region - Shifafure, Andreas Muronga (Rhodes University, Faculty of Education, Department of Education, 2015)
The National Curriculum of Education was implemented with the broad view of including all learners as laid out in the document Toward Education for All. The curriculum emphasised that the topic distillation should be studied. According to the Examiners Reports, the topic distillation is one of the topics where learners face difficulties in the Namibian Senior Secondary Certificate Ordinary (NSSCO) examination Grade 12. This led me to do research on understanding how Physical Science teachers mediate the topic distillation in Namibia specifically in the Kavango region. The study was carried out at two rural schools with two teachers teaching Grade 11. The community member who I asked to demonstrate the making of Kashipembe was also a participant during this study. Kashipembe is a local cultural brew alcohol beverage commonly made in the Kavango East and West Regions of Namibia, which was used as a learning context in this research study. The study used a qualitative case study underpinned by an interpretive paradigm. Data was generated through the use of document analysis, semi-structured interviews, stimulated recall interviews, lesson observations, brainstorming and practical demonstration of making Kashipembe. These different methods of data gathering were used with the aim of triangulating and validating the data. Therefore, my theoretical framework adopted Vygotsky's (1986) mediation of learning, social constructivism and pedagogical content knowledge according to Shulman's (1986) theory. The emergent themes were identified inductively and they were colour coded. These themes were later developed into analytic statements which were used in the study. The findings indicate that the use of community knowledge and experience during the teaching of scientific concepts like distillation is important. These findings can also be used by the practising teachers to make their teaching more effective in the curriculums where distillation is included. Therefore, the Namibian curriculum developers need to include this community knowledge in the curriculum to make it easier for the learners to make sense of the topic distillation.
Keywords: Science -- Study and teaching (Secondary) -- Namibia -- Kavango; Distillation -- Study and teaching (Secondary) -- Namibia -- Kavango; Teachers -- Training of -- Namibia -- Kavango; Community and school -- Namibia -- Kavango; Interdisciplinary approach to knowledge